If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -4)(x + 8) = 64 Reorder the terms: (-4 + x)(x + 8) = 64 Reorder the terms: (-4 + x)(8 + x) = 64 Multiply (-4 + x) * (8 + x) (-4(8 + x) + x(8 + x)) = 64 ((8 * -4 + x * -4) + x(8 + x)) = 64 ((-32 + -4x) + x(8 + x)) = 64 (-32 + -4x + (8 * x + x * x)) = 64 (-32 + -4x + (8x + x2)) = 64 Combine like terms: -4x + 8x = 4x (-32 + 4x + x2) = 64 Solving -32 + 4x + x2 = 64 Solving for variable 'x'. Reorder the terms: -32 + -64 + 4x + x2 = 64 + -64 Combine like terms: -32 + -64 = -96 -96 + 4x + x2 = 64 + -64 Combine like terms: 64 + -64 = 0 -96 + 4x + x2 = 0 Factor a trinomial. (-12 + -1x)(8 + -1x) = 0Subproblem 1
Set the factor '(-12 + -1x)' equal to zero and attempt to solve: Simplifying -12 + -1x = 0 Solving -12 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -1x = 0 + 12 Combine like terms: -12 + 12 = 0 0 + -1x = 0 + 12 -1x = 0 + 12 Combine like terms: 0 + 12 = 12 -1x = 12 Divide each side by '-1'. x = -12 Simplifying x = -12Subproblem 2
Set the factor '(8 + -1x)' equal to zero and attempt to solve: Simplifying 8 + -1x = 0 Solving 8 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -1x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -1x = 0 + -8 -1x = 0 + -8 Combine like terms: 0 + -8 = -8 -1x = -8 Divide each side by '-1'. x = 8 Simplifying x = 8Solution
x = {-12, 8}
| -13+y=-24 | | 13+y=-24 | | -13y=-24 | | 6x^3+4x=10x^2 | | 5x-7=3x-10 | | 5x+24(x-4)=107 | | 4x-3+2x=8x | | 6+k=14 | | (2x^2+3x-2)(3x^2-6x-5)= | | n-4=24 | | 23=-2(24-b)+3(b-3) | | 15x+21(x-2)=318 | | 4x^2+7-3=0 | | 19x-(4x-9)=84 | | 19x-3(4x-9)=84 | | 5m+10=9m-2 | | 5(6z+1)-9=146 | | 3(4x-1)=36 | | (-6)(9)= | | (4-9)= | | 4w^2=-12w-5 | | [10-2]= | | 12*-72= | | 14y=-84 | | v+-391=1255 | | v+-391=255 | | 8(4+4(5))= | | v+255=-391 | | 8(4+5(5))= | | -5(2x+1)=1-4(x+9) | | (x-5)(2x^2+3x-1)= | | 3(x+9)=42 |